Technological Leadership of School Heads and Teachers’ Technology Integration: Basis for the Development of a Training Program - Maala, Elenette B; Lagos, Fidelito D. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
Covid-19 pandemic saw the transition to online distance learning of the education in the Philippines. This became a challenge to both the teachers and heads of the educational institutions in terms of adapting and utilizing technology for better delivery and effective learning of students. The study aimed to determine the level of technological leadership of school heads. Using surveys and tests of collected data, it was revealed that the level of technological leadership of school heads based on technology innovation, technology assessment, technology forecasting, technology management and technology transfer shows a high overall weighted mean. These results showed that the technological leadership of school heads met the quality requirement of becoming technology leaders. Comparing this on teachers’ technology integration using z and t- test, the study also showed that both groups have similar insights regarding the level of technological leadership. The results and conclusions served as basis for developing a training program necessary to further address the needs of school heads and teachers.